COMPETITION COMPELLED IR RADIATIONS AND IR STIMULATED IN CAESIUM STEAMS - Bimagambetov, T. S. (Recent Contributions to Physics, 2018)
The competition stimulated IR radiation and IR stimulated Raman scattering in Cs vapours is researched in depending from concentration of atoms, intensive and frequency of the laser. Established, that at large concentration of atoms, also at high intensive and small ruins of laser the power of IR stimulatedRaman scattering behinds the mean of power of IR radiation. The theoretical interpretation of these process is given.